The Contextual Learning with Handout and Arthropodâs Preservation of High School Students Learning Outcomes - Oktaviani, Putri; Subekti, Niken; Lisdiana, Lisdiana (Journal of Biology Education, 2018)
The aim of the research is to determine the effectiveness of contextual learning with Handout and Arthropodâs preservation of high school students learning outcomes. The research was conducted at SMA N 1 Bulu Sukoharjo  Regency with research method by Pre-Experimental Design. The sample was X IA 1 and X IA 4 which taken by purposive sampling technique. The results showed that there was an influence on the results of psycomotor learning in the category very effective with percentage reach 85,94%, while the results of cognitive learning is in the category less effective with percentage 48%. The average of the students questionnaire responses after joining the learning was in very good criteria. Generally, the teacher and the students also gave good responses on the implementation of the learning. The conclusion of the research is the application of contextual learning with Handout and preserved Arthropodâs not yet effectively applied in learning.